A Platform for Manufacturing and Operation of Robot Systems - Demarchi, Arthur; Lang, Rafael Guedes; Silva, Ivan Nunes da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
The industry, since its beginnings, has developed itself through technological leaps aiming to improve its efficiency and productivity. Industry 4.0 is the most recent paradigm that promises to revolutionize production through the integration of information technology in all of its processes. It integrates manufacturing, operations, and maintenance in a single ecosystem comprised of a diverse range of IoT devices, artificial intelligence, and a huge amount of data. This paper elaborates on the implementation of Industry 4.0 concepts into the manufacturing and operation processes of a robotics competition team. The concepts were implemented through a web platform that integrates all of the group's manufacturing and operation processes in a single database. This aggregation is achieved by identifying each of the team's items using Unique Universal Identifiers (UUID). This identification makes it possible to register exactly which item is being used in each robot, when the robot was manufactured, the last time it had to go through maintenance, who has participated in each of those processes, etc. In addition, the web platform, being populated with the Bill of Materials and documentation of each project, is able to help the manufacturing process by supplying the student with a structured step-by-step guide and documentation on how to build each of the projects designed by the team. The Industry 4.0 platform, in that way, can both integrate and register everything that happens in the workshop and improve the processes by guiding the student through each step of the manufacturing process. Finally, for documentation and experimental evaluation, the processes that use the platform were modeled using Business Process Model and Notation (BPMN).